(untitled) (Research, Society and Development, 2021)
Being characterized as a fluid mosaic, the cell plasma membrane is a bilayer composed of phospholipids and proteins proposed by Singer and Nicolson in 1972. It is a fascinating three-dimensional structure with several functions such as allowing the integrity and transport of masses in and out of the cell. Especially in high school and elementary school, the subjects of Biology and Sciences, proper to Cytology, and they are seen by students as complex, abstract, making their visualization and understanding difficult, since they approach microscopic three-dimensional structures. To overcome such attempts and facilitate students’ learning, this article proposes a workshop with the objective of building and approaching a 3D didactic model of the plasma membrane of eukaryotic cells, using simple and low-cost materials. It is believed that the making and approach of this 3D model facilitated the understanding of the proposed topic, in addition to promoting greater motivation of students in the learning process, thus awakening the playful and creative side of students.